The Single Machine Weighted Mean Squared Deviation Problem - Vasquez-Perez, O (Elsevier B.V., 2017)
This paper studies a single machine problem related to the Just-In-Time (JIT) production objective in which the goal is to minimize the sum of weighted mean squared deviation of the completion times with respect to a common due date. In order to solve the problem, several structural and dominance properties of the optimal solution are investigated. These properties are then integrated within a branch-and-cut approach to solve a time-indexed formulation of the problem. The results of a computational experiment with the proposed algorithm show that the method is able to optimally solve instances with up to 300 jobs within reduced running times, improving other integer programming approaches. © 2017 Elsevier B.V.